Manifestations of Protest in Majid Darandash's Theatrical Texts M. Muhammad Ali Ibrahim Al-Asadi - Al-asadi, Mohammed Ali Ibrahim (lark, 2021)
Theatrical art, in general, has witnessed qualitative developments on the structural, artistic, and aesthetic levels. Theatrical art employs different aesthetics through the written text or presentation, and thus the aesthetics of the theater are based on the cognitive data in the aesthetic functions, and since the theater is a reflection of the image of the surrounding environment, it includes forms of protest is directly as a result of crises in general, so the protest has become employed in theatrical works as a tool to achieve communication with the recipient .This study included four chapters. The first chapter (the methodological framework) included the research problem, which was represented by the question about what manifestations represented the protest in the theatrical texts of Majid Darandash. Ages while the third topic dealt with the protest in the Iraqi dramatic text, then the chapter was concluded with the results of the theoretical framework. As for the third chapter, it included the research procedures, in which the researcher identified the research community and his deliberately chosen sample, in accordance with the research topic and its goal.
Keywords: protest, manifestation, text, Majid Darandash, theater, Iraq